Genetically engineered human muscle transplant enhances murine host neovascularization and myogenesis. (December 2018) - Perry, Luba; Landau, Shira; Flugelman, Moshe; Levenberg, Shulamit
Abstract Engineered tissues are a promising tool for addressing the growing need for tissues and organs in surgical reconstructions. Prevascularization of implanted tissues is expected to enhance survival prospects post transplantation and minimize deficiencies and/or hypoxia deeper in the tissue. Here, we fabricate a three-dimensional, prevascularized engineered muscle containing human myoblasts, genetically modified endothelial cells secreting angiopoietin 1 (ANGPT1) and genetically modified smooth muscle cells secreting vascular endothelial growth factor (VEGF). The genetically engineered human muscle shows enhanced host neovascularization and myogenesis following transplantation into a mouse host, compared to the non-secreting control. The vascular, genetically modified cells have been cleared for clinical trials and can be used to construct autologous vascularized tissues. Therefore, the described genetically engineered vascularized muscle has the potential to be fully translated to the clinical setting to overcome autologous tissue shortage and to accelerate host neovascularization and integration of engineered grafts following transplantation. Luba Perry et al. report transplantation of engineered prevascularized human muscle into mice to repair an abdominal muscle defect. They show that genetically engineering smooth muscle cells to secrete VEGF and endothelial cells to secrete ANGPT1 significantly improves host neovascularization and myogenesis.